Metodologias e práticas no ensino de Biologia sobre o sistema reprodutor humano e temas correlatos: uma abordagem através do ensino remoto - Gonçalves, Radamés Araujo (2022)
The knowledge about the anatomy and physiology of the human reproductive system is important for the youth realizes the changes that occur in their body; be able to perform a family planning; and protect himself from Sexually Transmitted Infections (STIs). The young people usually have many doubts about the human reproductive system and most of the time they are not able to discuss freely at home, seeking for information, often, with people who have limited knowledge, mistaken, or out of the context such as friends, neighbors, and even in television shows. Also, some teachers, despite of considering a relevant topic, have present difficulties of discussing it in the classroom. To fill this gap between the young and scientific knowledge about the human reproductive system, the school, especially the Biology teacher, has the role of being the mediator in the acquisition of the knowledge by students. Given this issue, the present work aims to develop didactic strategies to be used in remote Biology classes on the human reproductive system, aiming at student protagonism. In the work, the participatory method was used and has as theoretical-methodological assumptions the foundations of the qualitative approach, being developed through of the remote classes, using the Digital Technologies of Information and Communication (DTIC) as a means of communication, interaction and scientific investigation. Its target audience was students from four classes of the 3rd Grade of High School, regularly registered in a state school called State School Normal Padre Emídio Viana Correia, located in the city of Campina Grande - PB. The corpus of the work was collected through synchronous lessons taught by Google Meet, in which students performed activities such as: questionnaires, mural, audio recording and presentation, using the following Google Forms, Padlet, Podcast and PowerPoint, also were applied questionnaires to understand the students' prior knowledge (Pre-test) and post (Post-test), besides a semi-structured questionnaire about the learner satisfaction concerning the methodologies applied during the classes. The perception regarding the interaction of students with the teacher in remote classes was satisfactory, some had good prior knowledge about the topics covered, there was student protagonism when information on some topics were discussed, collecting information on the internet in real time and the questions formulated they were not restricted to the directing questions contained in the didactic sequences. There was shyness when discussing some specific topics, such as anatomy of the male reproductive system and the stages of human development. The students said that the face-to-face meetings would be better but they were satisfied with the dynamics of the classes via remote meeting, they reported that they understood the content and liked the activities offered. At the end of the work was developed a “Guide of Didactic sequence on the Human Reproductive System” to assist the Biology teacher in the teaching-learning process.